IDENTIFIKASI KUALITAS TANAH SAWAH PADA BEBERAPALOKASI DI LEMBAH PALU DENGAN METODE SKORING LOWERY - Rahmawati R. Lantoi; Saiful Darman; Yosep S. Patadungan (Universitas Tadulako, 2016)
The management of wetland rice lands particularly those in Lembah Palu are characterized by intensive tillage,excessive uses of inorganic fertilizers and pesticides as well as lack of organic fertilizer additions. Therefore, it is necessary to assess the quality of the wetland rice soils of Lembah Palu from the aspects of soil chemical and biological characteristics. The research aimed at identifying the chemical and biological qualities of the wetland rice soils in Lembah Palu. It was a descriptive-explorative research conducted from May to July 2015. Soil samples taken were from the wetland rice soil around Lembah Palu i.e. Sidondo, Sidera, Kaleke, Pantoloan, and Wombo. The soils were analyzed in the Soil Science Laboratory, Faculty of Agriculture of Tadulako University. The soil chemical parameters observed were pH, CEC, C-organic, N-total, P-total and K-total whereas that a biological parameter was the total soil microbes. The soil qualities were assessed using scoring technique based on the parameters determined. The research results indicated that the soils taken from Sidera, Sidondo and Kaleke have criteria of not healthy whereas those from Pantoloan and Wombo have criteria less healthy. Keywords: Biological Characteristics, Biological Properties Of The Soil, Soil Chemical, Soil Chemical Properties, Soil Quality, And Wetland Rice.